Rolling resistance of casters increases significantly after two years of simulated use - Wilson-Jene, Holly; Mhatre, Anand; Ott, Joseph; Krider, Benjamin; Smith, Clair; Terhorst, Lauren; Pearlman, Jonathan (Journal of rehabilitation and assistive technologies engineering, 2021)
Introduction Manual wheelchair propulsion is associated with upper limb pain and injury, and clinical guidelines recommend minimizing propulsive force to lower health risks. One of the strategies to reduce propulsive force is by minimizing rolling resistance (RR). Product testing studies suggest that RR of casters is affected by wear and tear which could have implications on the health risk of wheelchair users. The study will investigate the relationship between caster RR and environmental exposure using standard testing protocols. Methods RR of ten casters representing a range of diameters for different models of wheelchairs were measured before and after environmental exposure that includes corrosion, shock and abrasion simulating two years of community use. Results Four casters exhibited failures during durability testing, one catastrophically. Increases to RR after corrosion, shock and abrasion exposure were statistically significant using mixed-effects modeling, and four casters had increased RR greater than 20%. Conclusions Many of the casters evaluated exhibited increased RR forces and failure after environmental exposure. Improved caster design and use of corrosion resistant materials may reduce these failures. In addition, modification of the provision process could include replacement casters to reduce failures and avoid breakdowns that leave manual wheelchair users stranded or injured.